Rare and Complex Case Mimics Acute Myocardial Infarction: The Importance of Multimodality Imaging - Payne, Abby (JACC Case Rep, 2021)
We report a rare and complex case of cardiac sarcoidosis in a patient presenting with ventricular tachycardia. Multimodality imaging, along with clinical and histological examination, was essential in establishing the diagnosis of cardiac sarcoidosis. (Level of Difficulty: Beginner.)